Gender as a vehicle for the subordination of women maquiladora workers in Mexico. - KOPINAK, Kathryn (1995)
Shows that labour market dynamics among the maquila industries tend to trap women in the least-skilled jobs. Although the maquila sector was once celebrated for employing women, women's employment has gradually declined, and most female employees face discrimination in areas such as job training.